Adaptive mesh refinement for plane elements - Xue, Qiang; Worsak Kanok-Nukulchai; Pennung Warnitchai; Sugiyama, Toshiyuki; German Academic Exchange Service (DAAD) (Bangkok : Asian Institute of Technology, 1993)
he study of achieving economical finite element solution of specified accuracy is conducted, including three essential ingredients (i) a posteriori error estimating process, (ii) adaptive process, (iii) implementation of the predicted refinement. The Z2 -error estimator is adopted in the study to indicate the region where local refinement is needed. With hand h-p adaptive process, the refinement algorithm and the data structure for mesh enrichment of subdomain are presented. At last, plane stress/strain elements are cooperated as numerical examples.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng) - Asian Institute of Technology, 1993
Keywords: Numerical grid generation (Numerical analysis); Finite element method